PENGARUH PRAKTIK PEMBAGIAN MONEY POLITICS TERHADAP PERILAKU PEMILIH PADA PEMILIHAN CALON ANGGOTA LEGISLATIF TAHUN 2024 DI DESA PANUSUPAN, KECAMATAN CILONGOK, KABUPATEN BANYUMAS - Putri Puspita Ningtias; Fitriyah Fitriyah (Journal of Politic and Government Studies, 2026)
This research is motivated by the increasing trend of money politics in the 2024 Legislative Elections. This study aims to examine the effect of money politics on voter behavior in Desa Panusupan in the 2024 Legislative Elections. The research method used was quantitative explanatory research, with questionnaires distributed to 88 respondents. The hypothesis testing steps used included the classical assumption test, simple linear regression, the T-test, and the coefficient of determination test using SPSS version 23. The results indicate that the money politics distribution practices influence voter behavior, as calculated with the T-test; The Sig. value obtained was 0.000, meaning less than 0.05. Several findings that strengthen the effect of money politics distribution practices on voter behavior include the high intensity of the practice and public openness to accepting money politics.